Upaya Peningkatan Kompetensi Pendidik dalam Menyusun Silabus Dan RPP Melalui Supervisi Akademik yang Berkelanjutan Di MTsN 10 Tanah Datar - Rika Maria; Sufyarma Marsidin; Rifma Rifma (Universitas Batanghari Jambi, 2021)
The framework for developing the learning process includes three main activities, namely planning, implementation and evaluation. The learning planning process that must be carried out by an educator includes the following main activities: 1. Make an annual program 2. Make a syllabus 3. Make a semester program4. Make a learning implementation plan 5. Make a test/evaluation program. Of the five elements mentioned above, the syllabus and lesson plans are the minimum preparation for an educator when they want to teach. Based on the results of the analysis in the 2019/2020 school year at MTsN 10 Tanah Datar, there is a problem with the low quality of some educators who make lesson plans, especially the preparation of syllabus and lesson plans. To solve the problem of the weak performance of educators, a study was conducted to see how far the academic supervision of the madrasah principal can improve the competence of educators in preparing the syllabus and lesson plans. This mini research was carried out using the madrasah action research method which lasted for 2 cycles. Each cycle consists of stages of planning, implementation, observation and reflection. The results showed that continuous academic supervision has been scientifically proven to improve the competence of educators in preparing syllabus and lesson plans at MTsN 10 Tanah Datar. By increasing the competence of educators in compiling the syllabus and lesson plans, it is hoped that academic supervision activities will continue to be carried out regularly and educators will always be proactive in improving their competencies